2002
DOI: 10.1002/er.837
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and chemical contributions of added H2O and CO2 to major flame structures and NO emission characteristics in H2/N2 laminar diffusion flame

Abstract: SUMMARYNumerical simulation with detailed chemistry has been carried out to clearly discriminate the thermal and chemical contributions of added diluents (H 2 O and CO 2 ) to major flame structures and NO emission characteristics in H 2 /N 2 counterflow diffusion flame. The pertinence of GRI, Miller-Bowman, and their recent modified mechanisms are estimated for the combined fuel of H 2 , CO 2 , and N 2 . A virtual species X ; which displaces the individual CO 2 and H 2 O in the fuel sides, is introduced to sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 19 publications
(27 reference statements)
1
43
0
Order By: Relevance
“…The governing equations for mass, momentum, chemical species and energy, and the solution technique can be found in Lutz et al (1997). In this study, we retain the sink term due to the thermal radiation and details of the thermal radiation model, based on an optically thin approximation, can be found in the previous researches (Ju et al, 1997;Kim et al, 2002;Park et al, 2002aPark et al, -c, 2003a. The thermal radiation term is particularly involved due to its importance in the flame dynamics at low strain rates and the high gas radiation absorption coefficient such as CO 2 , CO, H 2 O, and CH 4 .…”
Section: Numerical Strategiesmentioning
confidence: 98%
See 2 more Smart Citations
“…The governing equations for mass, momentum, chemical species and energy, and the solution technique can be found in Lutz et al (1997). In this study, we retain the sink term due to the thermal radiation and details of the thermal radiation model, based on an optically thin approximation, can be found in the previous researches (Ju et al, 1997;Kim et al, 2002;Park et al, 2002aPark et al, -c, 2003a. The thermal radiation term is particularly involved due to its importance in the flame dynamics at low strain rates and the high gas radiation absorption coefficient such as CO 2 , CO, H 2 O, and CH 4 .…”
Section: Numerical Strategiesmentioning
confidence: 98%
“…The production of C 1 -and C 2 -chemical species, which mainly originated from the reaction CO 2 +H ! CO+OH, was a direct evidence of chemical effects, and thus as a result these chemical effects reduced the flame temperature and affected prompt NO in a complicated manner (Liu et al, 2001;Kim et al, 2002;Park et al, 2002aPark et al, -c, 2003a.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The temperatures at both fuel-and oxidizer-sides are 300 K, respectively. It was well recognized in the previous researches (Ju et al, 1997;Lee et al, 2001;Kim et al, 2002;Park et al, 2001) that especially at low strain rates the reduction of flame temperature was due to radiative heat loss. This was so because radiative heat loss is proportional to the volume of reaction zone and reaction zone thickness is physically inversely proportional to square root of strain rate.…”
Section: Resultsmentioning
confidence: 95%
“…Especially for the description of CO 2 -added flames Li and Williams (1999) took a different approach, which each with rate parameters were evaluated independently but might provide reasonable agreement with in references cited for other mechanisms. Park et al (2003b) took the basic skeleton with MillerBowman mechanism, and most of the rate parameters with the specific reaction rate constants were taken with those in the Li-Williams mechanism since the Miller-Bowman mechanism was less sensitive (Kim et al, 2002), and showed good agreement with the experimental data of Rrtveit et al (2002). The present study also adopted the reaction mechanism of Park et al (2003b), in which consists of 49 chemical species and 239 elementary reaction steps.…”
Section: Numerical Strategiesmentioning
confidence: 97%